Collaborative Feedback in Enhancing Master Level English Specializing Students’ Instructional Skills (Interdisciplinary Research in Education, 2024)
This study was conducted after identifying problems in the micro-teaching activities of M.Ed. fourth-semester English specializing students studying at Central Department of Education, Tribhuvan University in 2078 and 2079. The majority of the students had weaknesses in lesson planning, presentation, material selection, teaching strategies, text development and evaluation. As the internal supervisor, I proposed using collaborative feedback to address these issues. The study aimed to assess the effectiveness of collaborative feedback in improving students' instructional skills and engagement. Using a Participatory Action Research (PAR) design and involving 22 students in nine rounds of micro/peer teaching, data were collected through peer/teacher evaluations, classroom observations of each student, and Focus Group Discussions (FGDs). The data were analyzed thematically. The findings indicate that collaborative feedback helped students identify their areas of strengths and weaknesses in presentation skills, classroom interaction, and material construction and use leading to better lesson planning, teaching strategies and overall teaching skills. Collaborative feedback offered opportunities for learning from others, increased motivation and receptivity to feedback.